1988
DOI: 10.1159/000128759
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Partial Ischemia and Reflow on Mitochondrial Metabolism in Rat Liver

Abstract: To clarify the effects of partial ischemia and reflow on the mitochondrial metabolism of the rat liver, the afferent vessels supplying the left lateral and left half of medial lobes were occluded and then reperfused after given time periods of ischemia (30, 60, 90 and 120 min, groups A, B, C and D, respectively). Samplings were taken at 0, 10 and 60 min after reperfusion. The energy charge levels of ischemic lobes decreased rapidly from 0.85 ± 0.01 in the sham group to 0.38 ± 0.11, 0.35 ± 0.07 and 0.34 ± 0.06 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…In contrast to ischemic lobes, non-ischemic lobes showed an enhanced OPR during ischemia and reperfusion in both control and a-tocopherol groups. This result was coincident with the findings of Wang et al [21], who indicated that an increased OPR in non-ischemic lobes at the end of ischemia resembled a phenomenon seen in major partial hepatectomy. However, the increase in OPR after reperfusion in the present study was not so marked as they reported.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast to ischemic lobes, non-ischemic lobes showed an enhanced OPR during ischemia and reperfusion in both control and a-tocopherol groups. This result was coincident with the findings of Wang et al [21], who indicated that an increased OPR in non-ischemic lobes at the end of ischemia resembled a phenomenon seen in major partial hepatectomy. However, the increase in OPR after reperfusion in the present study was not so marked as they reported.…”
Section: Discussionsupporting
confidence: 91%
“…Reperfusion has been reported to accelerate mitochondrial oxidative phosphorylation in the non-ischemic lobes of partial ischemia-reperfusion models, whereas the ischemic lobes show suppressed mitochondrial functions. This fact may indicate that the liver as a whole is capable of maintaining its function even under hypoxic stress [21]. However, no detailed study has been conducted to examine glucose tolerance and mitochondrial function during ischemia-reperfusion in the presence and absence of radical scavengers during supplementation with glucose.…”
mentioning
confidence: 99%
“…Liver cells may be resistant to ischemia for 30 to 60 minutes, but irreversible cell damage is usually seen over a longer period of time. After 60 minutes of ischemia, SORs begin to increase at 5 minutes of reperfusion and then peak at 15 minutes of reperfusion [8]. SORs, which occur due to I-R injury, cause damage to both liver parenchyma and other liver cells [2].…”
Section: Discussionmentioning
confidence: 99%
“…SORs are destroyed by cellular defense mechanisms. When SORs are destroyed, enzymatic pathways such as SOD, GPx, and catalase (Cat) are activated [8][9][10][11][12][13][14]. Numerous substances, which are thought to be effective by enzymatic or non-enzymatic pathways, have been experimentally tested in order to reduce ischemic reperfusion injury in the liver and other tissues, but there are not still products that have been actively applied for treatment [3,5,6].…”
Section: Discussionmentioning
confidence: 99%
“…The adequacy of our modified model in simulating the damaged liver in chronic hepatitis or the precirrhotic liver was affirmed by the poor survival rate after warm ischemic intervention: Cirrhotic patients are clinically more vulnerable to hepatic ischemia than patients with a normal liver. In situ occlusion of hepatic blood inflow for 30 minutes causes liver failure in rats [17]. In our previous experiment, the survival rate on postoperative day 7 after this intervention in normal rats was 50%, whereas the survival rate of the rats with fibrotic livers was only 21% [8].…”
Section: Discussionmentioning
confidence: 99%